Adiponectin and Carotid Intima-Media Thickness in the Northern Manhattan Study - Gardener, Hannah (2011)
BACKGROUND AND PURPOSE: Adiponectin is an insulin-sensitizing plasma protein expressed in adipose tissue and suggested to play a role in atherosclerosis and cardiovascular disease. Data are lacking on the relationship between adiponectin and carotid intima-media thickness (IMT) in ethnically heterogeneous populations. We examined the relationship between adiponectin and IMT, a marker of atherosclerosis, in a multi-ethnic cohort study of stroke risk factors. METHODS: Participants were from the Northern Manhattan Study (N=1522, mean age 66±9 years, 60% female, 20% black, 18% white, 60% Hispanic). Adiponectin was measured from baseline plasma samples and IMT was assessed by high-resolution B-mode carotid ultrasound. Regression models were used to examine the association between adiponectin, assessed continuously and in quartiles, and IMT, controlling for demographics and vascular risk factors. RESULTS: The mean adiponectin level was 10.3±5.2 μg/ml (median=9.2, range=2.3-53.3), and the mean IMT was 0.91±0.08 mm. Adiponectin was inversely associated with IMT, even after controlling for demographics and vascular risk factors. Individuals in the first quartile of adiponectin had mean IMT that was on average 0.02 mm greater than those in the top quartile. The relationship between adiponectin and IMT appeared to be stronger among those with diabetes. CONCLUSION: Our findings suggest that low adiponectin is associated with increased IMT in a multi-ethnic cohort and support a protective role for adiponectin in atherosclerosis.